"Health discourses as moral communication? Linguistic case studies from Côte d'Ivoire and Cameroon" (Presenting The Cluster Projects, 2022)
In this video, Prof. Dr. Martina Drescher and Dr. Oumarou Boukari talk about their research project "Health discourses as moral communication? Linguistic case studies from Côte d'Ivoire and Cameroon" that they conduct as part of the Cluster's research section "Moralities". The project examines manifestations of ethics or morality – two concepts we use interchangeably – in everyday talk by zooming in on health communication in Cameroon and Ivory Coast. It draws on constructivist and phenomenological conceptualizations of ethics by assuming that there are no moral phenomena as such, but that ethics is intimately tied to interaction. More info on the project here: https://www.africamultiple.uni-bayreuth.de/en/Projects/Moralities/Moralities_Health_Drescher/index.php